The Effect of Entrepreneurship Study Interest on the Interest of Students in Private Vocational School of Pusri Palembang Academic Year 2020/2021 - kadek manik trusniawati; Neta Dian Lestari; Nova Pratiwi (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: The research objective was to determine the effect of entrepreneurship subjects on students' interest in becoming entrepreneurs at SMA PUSRI Palembang for the academic year 2020/2021. Design/methodology/approach: This research uses quantitative methods; data collection techniques used documentation, interviews, and questionnaires. The total population of the study was all class XI SMA PUSRI, amounting to 120. Sampling using is simple random sampling as many as 91 students. Findings: Based on the results of the discussion of the influence of entrepreneurship subjects on students' interest in becoming entrepreneurs, it was obtained that the average learning outcome was 78.1% of entrepreneurial subjects with good criteria. Meanwhile, students' interest in becoming entrepreneurs is included in a quite interesting category. The indicators of interest in entrepreneurship that are measured include; The percentage of self-confidence indicators is 65%, the task and result orientation indicators are 63%, the risk-taking indicators are 70%, the leading indicators are 64%, the future-oriented indicators are 62%, the creative and constructive thinking indicators are 64% and the attitude indicators honest and responsibility of 73%. The conclusion from the results of data analysis, there is an influence of entrepreneurship subjects on students' interest in becoming entrepreneurs at PUSRI Palembang High School for the 2020/2021 academic year. Research limitations/implications: This research is conducted at SMA PUSRI Palembang where they are still relatively young and may not think about work. Practical implications: The result of this research can be used as a reference in increasing student interest in becoming entrepreneurship. Originality/value: This research is conducted at SMA PUSRI Palembang at the early 2020/2021 academic year. Paper type: Research paper.